2005
DOI: 10.1177/0092070305277385
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Major-League Sports' Official Sponsorship Announcements and the Stock Prices of Sponsoring Firms

Abstract: This study presents analysis of the impact of “official product” sports sponsorships with the National Football League (NFL), Major League Baseball (MLB), the National Hockey League (NHL), the National Basketball Association (NBA), and the Professional Golfers Association (PGA) on the stock prices of sponsoring firms. The primary finding of the study is that, in the main, announcements were accompanied by increases in shareholder wealth. The 53 sponsors analyzed experienced mean increases in stock valuations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
122
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 21 publications
8
122
1
3
Order By: Relevance
“…Examples include sponsorship announcements, as in Cornwell et al (2005); Clark et al (2009) and corporate event sponsorships, as in Mishra et al (1997). 4 Clark et al (2009) analyze the impact of title event sponsorship announcements on shareholder wealth of the sponsors.…”
mentioning
confidence: 99%
“…Examples include sponsorship announcements, as in Cornwell et al (2005); Clark et al (2009) and corporate event sponsorships, as in Mishra et al (1997). 4 Clark et al (2009) analyze the impact of title event sponsorship announcements on shareholder wealth of the sponsors.…”
mentioning
confidence: 99%
“…Prior sponsorship impact research has found positive effects upon brand equity and even stock price of sponsoring brands following a sponsorship announcement (e.g., Cornwell, Pruitt, & Clark, 2005), and the Study 2 findings reflect this halo effect of a sponsorship announcement, with the interactive effect found for sponsorship availability. Hence, explicit and repeated communication of the sponsorship relationship through the sponsorship-linked advertising and press releases is recommended as an activation strategy for sponsors.…”
Section: Sponsorship Linked Advertising 30mentioning
confidence: 59%
“…To capture the effects on the stock price and shareholder value, event-study methodology is broadly applied in the finance, economics, and accounting literature, and more recently in the marketing literature (e.g., Cornwell, Pruitt, & Clark, 2005;Evans, 2010). This study follows previous marketing literature and applies event-study methodology to examine effects to the shareholder.…”
Section: Investorsmentioning
confidence: 99%